Proses sosialisasi anak di sekolah: Dari bangku kelas hingga lingkungan pergaulan - Fadlilah, Ziyadah; Khasanah, Nur (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
ABSTRACT This study aims to examine how students learn values and norms from the perspective of Islamic sociology of education, focusing on the role of family and school as primary determinants in shaping a child's personality. The method used was library research, collecting and analyzing various sources such as books, journals, and relevant previous research. The results indicate that socialization occurs in two main stages: primary socialization, which occurs within the family environment, and secondary socialization, which occurs at school. Within the family, children receive basic values and norms through affection, emotional support, and guidance from parents. At school, teachers act as coaches and role models, helping students understand moral, social, and religious values through concrete examples and a learning approach appropriate to the child's developmental stage, based on Jean Piaget's theory. This study concludes that collaboration between family, school, and community is crucial in creating a positive socialization process, thus developing students with strong character, good morals, and the ability to adapt positively to their social environment.